2022
DOI: 10.5041/rmmj.10484
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Open Fronto-Facial Resection for Fungal Osteomyelitis of Frontal Bone

Abstract: Introduction: The second wave of coronavirus disease 2019 (COVID-19) led to the resurgence of opportunistic infections due to the injudicious use of steroids. Sinonasal mucormycosis was declared an epidemic in India during the pandemic. Mucormycosis was managed effectively by surgical debridement along with systemic amphotericin B. Currently, a resurgence of mucormycosis following initial treatment, in the form of fungal osteomyelitis of the frontal bone, is being seen in India. Methods: This prospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…18 , 19 , 20 Significant cranial vault osteomyelitis secondary to ROCM was also seen, albeit less frequently. 7 , 8 , 9 , 12 , 13 , 21 , 22 However, presentation as PPT has been rarely described during either the pre-pandemic 6 or pandemic eras, 11 both publications being single case reports in adult patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 , 19 , 20 Significant cranial vault osteomyelitis secondary to ROCM was also seen, albeit less frequently. 7 , 8 , 9 , 12 , 13 , 21 , 22 However, presentation as PPT has been rarely described during either the pre-pandemic 6 or pandemic eras, 11 both publications being single case reports in adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other series have described a craniotomy approach for similar cases. 7 , 8 , 9 Our own experience with 19 patients with ROCM and frontal osteomyelitis without PPT showed that there was no need to re-explore patients via either an open or endoscopic approach if the initial endoscopic debridement using a standard protocol was performed and followed up with antifungal therapy and regular cavity cleaning of the operated sinuses. We applied the same protocol for the management of patients with extensive skull base osteomyelitis too, with good outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation